2019
DOI: 10.3389/fphys.2019.00844
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory, Oxidative Stress, and Angiogenic Growth Factor Responses to Repeated-Sprint Exercise in Hypoxia

Abstract: The present study was designed to determine the effects of repeated-sprint exercise in moderate hypoxia on inflammatory, muscle damage, oxidative stress, and angiogenic growth factor responses among athletes. Ten male college track and field sprinters [mean ± standard error (SE): age, 20.9 ± 0.1 years; height, 175.7 ± 1.9 cm; body weight, 67.3 ± 2.0 kg] performed two exercise trials in either hypoxia [HYPO; fraction of inspired oxygen (F i O 2 ), 14.5%] or normoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Even though it is a necessary defensive reaction that helps damaged tissue to recover, it can also cause other diseases like cardiovascular disease [ 23 ] and is closely related to musculoskeletal damage and muscle fatigue [ 24 , 25 ]. In some previous studies [ 6 , 26 ], the levels of fibrinogen, IL-6, and TNF-α in the blood have been reported to be indices reflecting the inflammatory response induced by acute exercise. This study analyzed the levels of plasma fibrinogen, serum IL-6, and TNF-α to verify changes in the inflammatory response depending upon the exercise performed in NN and HH environments and investigated the effect of HBOT on recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though it is a necessary defensive reaction that helps damaged tissue to recover, it can also cause other diseases like cardiovascular disease [ 23 ] and is closely related to musculoskeletal damage and muscle fatigue [ 24 , 25 ]. In some previous studies [ 6 , 26 ], the levels of fibrinogen, IL-6, and TNF-α in the blood have been reported to be indices reflecting the inflammatory response induced by acute exercise. This study analyzed the levels of plasma fibrinogen, serum IL-6, and TNF-α to verify changes in the inflammatory response depending upon the exercise performed in NN and HH environments and investigated the effect of HBOT on recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the fibrinogen and IL-6 levels were significantly increased after the race. Furthermore, Kasai et al [ 26 ] conducted a repeated sprint exercise with 10 male athletes in hypoxic (fraction of inspired oxygen (F i O 2 = 14.5%, equivalent to a simulated altitude of 3000 m) and normoxic (F i O 2 = 20.9%) conditions. Although the levels of IL-6 increased significantly after exercise in both conditions, there was no significant difference in levels between the two environmental conditions, which supports the results of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [ 26 ] found that VEGF plays vital roles in hypoxia responses by controlling the expression of numerous hypoxia-responsive genes functioning in diverse processes of oxygen delivery. In addition, an investigation has shown that VEGF not only regulates oxygen supply and growth but also acts as a mediator of inflammatory cytokines [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [34] found that VEGF plays vital roles in hypoxia responses by controlling the expression of numerous hypoxia-responsive genes functioning in diverse processes of oxygen delivery. In addition, an investigation has shown that VEGF not only regulates oxygen supply and growth but also acts as a mediator of in ammatory cytokines [35].…”
Section: Discussionmentioning
confidence: 99%